Metal matrix composites : synthesis, wear characteristics, machinability study of MMC brake drum /: synthesis, wear characteristics, machinability study of MMC brake drum. ([2014]) - Natarajan, Nanjappan; Krishnaraj, V (Vijayan); Davim, J. Paulo
No abstract available